Critical reflections: experiencing discrimination, disrespect and disregard and formations of professional identity - Madileng, Mary M (South African Journal of Higher Education, 2016)
This article offers a brief account of some critical incidents in my educational journey as a learner and teacher in South African schools and universities and an analysis of the influence of these incidents on the formation of my professional identity. It examines how social interactions and engagement with peers and students have helped construct and reconstruct my professional identity, allowing me to better recognize myself as an educator shaped by experiences of various forms of discrimination, disrespect and disregard. These experiences and my critical reflection on them have proved valuable for the development of my personal ‘voice’ as a reflective professional. I argue that the process of critical reflection has led to a deeper understanding of how negative (and some positive) experiences in my journey from rural primary school learner to university lecturer have been positive for strengthening my determination to succeed academically and to be the kind of teacher in the academy who aims to be respectful and supportive of all students. Keywords: critical reflections, epistemic injustice, professional identity, discrimination, disrespect, disregard